Leader Turnover, Volatility, and Political Risk. Issue 3 (June 2014) - Fails, Matthew D.
<x xml:space="preserve">Abstract</x> On average, democracy reduces political risk for foreign investors, yet this emphasis on regime type obscures the tremendous variation within autocracies. Moreover, conventional explanations emphasizing the role of checks and balances are ill‐suited to explain why some autocracies, which typically lack these features, are associated with such low‐risk environments. This article explains variations in political risk by emphasizing the role of autocratic leader replacement. Autocrats select from a heterogeneous mixture of private goods to appease narrow‐winning coalitions. Leader replacement in such regimes is, therefore, associated with new winning coalitions and new private goods. When turnover is frequent, the policy environment becomes more volatile and political risk increases relative to autocracies with more stable leadership. Importantly, the risk‐increasing effect of turnover holds for both irregular and rule‐bound leader transitions in autocracies. These predictions are strongly supported through cross‐national quantitative analysis employing a new measure of leaders' risk of political replacement.